Knowledge, attitudes and practices of private dentists in Bulacan on abutment tooth preparation for removable partial denture service - Espares, Denica Jena E.
Removable partial prosthodontics is the field of dentistry that deals with the replacement of missing dental and oral structures with a fabricated prosthesis. One factor considered in creating a design for an RPD is the need for an abutment tooth preparation which is the pre-prosthetic modification of a sound abutment to facilitate the placement of the denture. Previous studies have shown that dentists rarely do any preparatory intraoral procedure and most general practitioners neglect fundamental RPD principles. The knowledge and attitude are the bases in creating the design of the RPD for each patient while the realization of this design is determined by the practice of the dentist. At present, there is no recognized standard of care in the dental services rendered in the Philippines. The results of this study may help in the establishment of the standard of care in RPD prosthodontics through the provision of data on the attitudes and practices of dentists with regard to tooth preparations for RPD service. Methods: Purposive sampling was done to select the participants of the study. A sample size of 92 was computed using the formula for finite population with a 95% confidence level and 5% margin of error. Informed consent forms and self-administered questionnaires consisting of 24 questions on knowledge, attitudes and practices of dentists on abutment tooth preparation of RPD service were given to participants. Pearson Chi Square test was done to determine the association of demographics to knowledge, attitudes and practices. Paired t-test was done to assess the correlation among the three categories. Results: There is no statistically significant association between demographics and knowledge, attitude and practices of Kadebu dentists on abutment tooth preparations for RPD service. Only 57% of Kadebu dentists passed the knowledge test. 95% of the participants feel that abutment tooth preparations for routine RPD service. Both high knowledge and positive attitude are translated into positive practice. However, high knowledge of the dentist does not necessarily mean that their attitude is positive. Conclusion: The active members of Kadebu for the year 2012-2013 do not have adequate knowledge on abutment tooth preparations for RPD service. They also do not agree that these are necessary and they do not routinely perform these for RPD service.